PENGEMBANGAN MODUL TERAPI SURAH AL-MU’MINUN AYAT 97-98 UNTUK MENGURANGI KECEMASAN UMUM SISWA DI SMK N 3 PEKANBARU - Ainul Betri; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This study aims to develop a module in reducing students' general anxiety. The type of research used is Research and Development (R&D) level 1. To develop a better module, in this study a validation test was carried out from material experts. Data collection techniques used interviews and validation questionnaires. The results of the study where the procedure for developing the Al-Quran therapy module in Surah Al-Mu'minun Verses 97-98 in reducing students' anxiety levels had been carried out in accordance with the procedure through 5 stages, namely: a. Potential and problems; b. Collection of data or information; c. Product design; d. Design validation; e. Proven design. After validation, it can be concluded that the therapy module of the Koran Surah Al-Mu'minun Verses 97-98 in reducing the level of anxiety of students developed is feasible to be applied in the learning process.Key Words : Module Development, Al-Qur'an Therapy, and Surah Al - Mu'minun Verses 97-98